Dysfunctional Behavior Atas Interaksi Reinforcement Contigency Dan Motivasi Ekstrinsik Subordinate - Fara Fitriyani; Emma Suryani (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2018)
This study aims to determine the effect of compliance pressure on budgetary slack and the interaction between compliance pressure and strengthening contingency on budgetary slack. The population of this study is subordinate to a college in Banten Province. The sampling method uses purposive sampling with a number of samples that meet the criteria of 91 respondents. The questionnaire was tested by reliability test and validity test, then the classical assumptions were tested including normality test, multicollinearity test, and heteroscedasticity test. Then hypothesis testing is done by single regression analysis and multiple regression analysis. The results show that all variables are reliable and valid and meet the classic assumption test. The results of hypothesis analysis indicate that compliance pressure affects budgetary slack, there is an interaction between compliance pressure and a strengthening contingency on budgetary slack.